"Factors Affecting agency’s costs "Applied Study on Commercial Banks Listed at the Amman Stock Exchange - Chakour, Omar Farid (Arab Journal for Sciences and Research Publishing, 2017)
This study aims to identify the factors affecting in the agency’s costs in commercial banks listed at the ASE, and to achieve this goal, the researcher studying the impact of a some factors in reducing agency costs, these factors are the board size, the percentage of independent members of the board, the number of the audit Committee meetings, institutional ownership, family ownership, ownership concentration, debt financing, the bank market share, and the bank size, and the agency costs is measured using three indicators, the asset turnover index, operating expenses index, and free cash flow index. The study sample composed of all commercial banks listed on the Amman Stock Exchange, which have data in the Amman Stock Exchange during the study period (2013 - 2015), which is sixteen banks, and used Excel program and Statistical Package for Social Sciences to identify the descriptive characteristics of the variables of the study, and analysis of their data, and was also used regression analysis method to test hypotheses of the study. Study results that the Agency’s costs increased with increasing of board size, the independent member’s ratio, the number of meetings of the Audit Committee, institutional ownership, the family ownership, financing debt, and the bank market share, and it decreases with increasing ownership concentration according to turnover of assets index. The results of the study showed, according to operating expenses index, that the Agency’s costs increased with increasing debt financing and concentration of ownership, and decreases with increasing board size and increase the family ownership, but for the free cash flow index, the results of the study showed that the Agency’s costs increase with the board size, and decreases with increasing concentration of ownership.